Why Partnering with HR During Organization Change Matters: It Is Not Just about Moving Boxes. Issue 1 (13th January 2019) - Andia, Lynne
Abstract: Successful organization change demands more than paying attention to the new structure and new reporting relationships. More is needed, and the HR function and its internal consulting partners enable that change by leading the effort to ensure employees can commit to the change.